Tackling health inequalities in prostate cancer: the Man Van project. Issue 2 (6th February 2023) - Simson, Nick
Abstract : There are stark health care inequalities that exist in prostate cancer in the UK. The Man Van is a new pilot project from the team at The Royal Marsden, The Institute of Cancer Research and RM Partners that aims to help bridge some of the gaps.